The Analysis of The Influence Work Experience and Work Culture on Performance of Islamic School Teachers. - Suwarsito Suwarsito; Stellamaris Metekohy; Nersiwad Nersiwad; Nur Alam; Muh. Risal Tawil (Departement of Mathematics Education, 2023)
This form of investigation employs a quantitative methodology. The method of gathering data takes the form of a survey. The participants in the study were educators, with a total of 20 teachers. The findings of the analysis indicated that the workplace culture has a noteworthy impact on teacher performance, accounting for 35.3%. Conversely, work experience was found to have no significant effect on teacher performance, contributing only 72%. It is important to note that to acquire good work experience, a teacher must possess the necessary skills and knowledge. The research also revealed that there is a significant correlation between work culture and work experience on teacher performance, contributing 35.8%. To enhance teacher performance, it is recommended that teachers cultivate a sense of enthusiasm and dedication when implementing the established school culture and acquire knowledge that aligns with their educational background